2022
DOI: 10.1088/1757-899x/1248/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and 3D Printing of Silver Nanoparticles/Photopolymer Resin Composites

Abstract: Recent advancements in the synthesis, functionalization, and processing of metal nanoparticles to enhance the properties of polymers have gained interest in the research community. Researchers have conducted several studies to exploit the extraordinary properties of metal nanoparticles, especially when mixed with polymers. This study investigates the adaptability of synthesized polymer resin nanocomposites, tailoring the physical and thermal properties of photopolymer resins with controlled dispersion of silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The SAW package prototype in a flip-chip configuration showed a significant signal-to-noise ratio (SNR) of about 30 dB via an antenna-bridged radio frequency link at a moderate distance of 3 cm. Ikram et al [255] also reported the effects of silver nanoparticles on the physical and thermal behaviour of polymethylmethacrylate (PMMA) photopolymer resin using SLA 3DP. The study showed that the incorporation of silver 2 wt% improved the thermal stability by 6.6% and decreased weight loss by about 8%, compared to the unmodified resin.…”
Section: Other Nanoparticle-modified Polymeric Resinmentioning
confidence: 99%
“…The SAW package prototype in a flip-chip configuration showed a significant signal-to-noise ratio (SNR) of about 30 dB via an antenna-bridged radio frequency link at a moderate distance of 3 cm. Ikram et al [255] also reported the effects of silver nanoparticles on the physical and thermal behaviour of polymethylmethacrylate (PMMA) photopolymer resin using SLA 3DP. The study showed that the incorporation of silver 2 wt% improved the thermal stability by 6.6% and decreased weight loss by about 8%, compared to the unmodified resin.…”
Section: Other Nanoparticle-modified Polymeric Resinmentioning
confidence: 99%